Implementasi Strategi Pengembangan UMKM Kirantea dengan Metode SWOT dalam Upaya Meningkatkan Daya Saing di Pasar - Andri Herlambang; Yuli Setiawannie; Syahputra Amry; Nita Marikena; Andisyah Johan (Lembaga Pengembangan Kinerja Dosen, 2025)
Business development, especially in the culinary industry. UMKM Kirantea is one of the businesses in the culinary sector that uses SWOT analysis to develop its business strategy. As part of this research, a SWOT analysis was carried out to determine the position of UMKM Kirantea in the culinary industry and identify strengths, weaknesses, opportunities and threats related to processing and developing its business. Based on the results of the SWOT analysis, UMKM Kirantea can continue to develop, but a combination of SWOT analysis is needed, such as implementing SO strategies, one example of which is expanding cooperation networks and networking with stakeholders (associations, restaurants, hotels) holding event activities in various regions, strategies WO, one example is increasing cooperation and networking with suppliers and partnerships with medium and large scale industries as well as using local or regional events as a promotional tool, ST strategy, one of which is maintaining affordable prices and quality-controlled materials to face competition and WT strategies, such as developing an online marketing platform to remain competitive amidst competition.